Incorporating Hijaiyah Sounds in English Pronunciation Class: Students’ Perception - Gusdian, Rosalin Ismayoeng; Lestiono, Riski (JEES (Journal of English Educators Society), 2020)
Indonesian students still find it perplexing to acquire English pronunciation as both Bahasa as their mother tongue and English do not share equivalent phonological and phonetic systems. Meanwhile, Arabic (in this case is their Hijaiyah sounds) is proven to share some phonological resemblance to some English sounds. Therefore, it is the aim of the study to investigate the student perception of the implementation of Hjaiyah sounds in their English pronunciation class. The study employed a descriptive research design as the approach. The participants of the study were 36 students of the English Study Program in the academic year of 2019/2020. These participants were third-semester students undertaking their Intermediate Speaking class. Questionnaire and interview guide were utilized as data instruments. In collecting the data, some procedures including distributing the questionnaire and conducting the interview were carried out. In data analysis, the data from the survey were transformed into a percentage to obtain a more general image of the data description. The data from the interview were also transcribed. Finally, the findings were examined and discussed using both narrative and numerical description. As a result, this study has confirmed that the implementation of Hijaiyah sounds in teaching English pronunciation is perceived positively by the students. HIGHLIGHTS: Indonesian students still find it perplexing to acquire English pronunciation as both Bahasa as their mother tongue and English do not share equivalent phonological and phonetic systems. Arabic (in this case is students' Hijaiyah sounds) is proven to share some phonological resemblance to some English sounds.